Low-cost measurement light intensity and efficiency of the lamp For school purposes in science experiment - Tegar Saputra, Winata; Cahya Prima, Eka; Riandi (Research in Physics Education, 2023)
The purpose of this research is to assist science teachers in carrying out experiments in science classes, particularly physics classes, to ascertain the optimal light intensity and efficiency of various lamp types made of inexpensive materials that are related to scientific concepts. The purpose of this study was to develop a practical learning technique based on experiments to measure the lamp’s energy efficiency and light intensity. Three different types of bulbs were used in this research experiment: CFL, LED, and incandescent. Students select a lamp after the experiment based on observations of light intensity and calculations of the lamp’s efficiency using a solar power meter and efficiency equation. The light intensity of the LED lamp shows the highest value with 18,66W/m2 rather than Compact Fluorescent lamp with 15,05% and incandescent lamp with 0,02%. While the efficiency of the LED lamp is 52,6%, the CFL is 26,89%, and the incandescent lamp is 11,26% Novelty: There is not a lot of study on the measurement of light intensity and the calculation of lamp efficiency using inexpensive materials for science-related student experiments.